The Relationship between Self-Confidence and Social Support and Career Anxiety in Buddhist Students - Sari, Fipit Nurika; Santi, Dyan Evita; Suryanto (Journal of Information Systems and Management (JISMA), 2024)
Obtaining or getting a job is generally a career achievement that occurs when individuals enter adulthood. This can trigger anxiety, especially in individuals in the changing times who are generally just starting a career, such as a student who has completed his studies. This study aims to determine the relationship between self-confidence and social support with career anxiety in Buddhist students. The sample in this study was 80 Buddhist students using purposive sampling. The data analysis method in this study uses multiple linear regression techniques. The results showed that in the first hypothesis test, there is a significant relationship between self-confidence and career anxiety. The second hypothesis shows that there is a significant relationship between social support and career anxiety. The third hypothesis shows that self-confidence and social support simultaneously have a significant effect on career anxiety in Buddhist students.